When Halal is not Enough: The Paradox of Moral Activism Beyond Ethnocentrism and Religious Commitment - Alfian Budi Primanto; Rahmawati Rahmawati; Nita Ani Dia Utami (Journal of Digital Marketing and Halal Industry, 2025)
Muslim consumers increasingly consider factors beyond halal compliance when evaluating brands, particularly when brands are perceived to be associated with humanitarian issues; halal status alone may no longer be sufficient to sustain favourable consumer responses, creating a critical dilemma in Muslim markets. While prior studies have highlighted consumer animosity and ethnocentrism as drivers of brand avoidance, limited attention has been paid to the psychological mechanisms through which these factors translate into unwillingness to buy. Specifically, the mediating role of brand attitude, the behavioral relevance of perceived boycott efficacy, and the moderating influence of religious commitment remain underexplored. Addressing this gap, the present study examines unwillingness to buy among Muslim consumers by investigating how brand attitude mediates, and religious commitment moderates, the effects of consumer animosity, consumer ethnocentrism, and perceived boycott efficacy. Using a quantitative design, survey data were collected from Muslim respondents through purposive and snowball sampling and analyzed using the PROCESS Macro in SPSS. The findings demonstrate that brand attitude serves as a central mediating mechanism, particularly for consumer animosity and perceived boycott efficacy, translating moral emotions and beliefs into avoidance behavior. In contrast, consumer ethnocentrism and religious commitment show no significant direct or moderating effects, indicating that purchase resistance in humanitarian conflict contexts is driven less by nationalistic ideology or religiosity and more by negative moral evaluations of brands and perceptions of collective action effectiveness. These results reinforce the view that contemporary Muslim consumer boycotts function as value-driven, brand-specific moral responses rather than expressions of ethnocentric or purely religious consumption.